2010
DOI: 10.3892/ijo_00000674
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism of malignant cells is not regulated by transketolase-like (TKTL)-1

Abstract: Abstract. An isoenzyme of transketolase, transketolase-like (TKTL)-1, has been hypothesized to play a pivotal role in the pathophysiology of malignant tumors. Available data are based on the detection of the putative TKTL-1 protein with one particular mouse monoclonal anti-TKTL-1 antibody, clone JFC12T10. In this study it was demonstrated that a) JFC12T10 detects multiple unspecific bands in Western blots, b) a 75-kDa band hitherto referred to as TKTL-1 corresponds to a nuclear protein and c) immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…There is evidence that suggests that the role of TKTL1 may not be well understood. Mayer et al [ 159 ] used real-time PCR to investigate the presence of the TKTL1 gene in six different malignant cell lines and failed to find any evidence for the expression of this gene. In addition, they repeated the immunohistochemical studies using the same antibody used by the Langbein group [ 158 ] and reported staining of multiple unspecific bands in Western blots.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that suggests that the role of TKTL1 may not be well understood. Mayer et al [ 159 ] used real-time PCR to investigate the presence of the TKTL1 gene in six different malignant cell lines and failed to find any evidence for the expression of this gene. In addition, they repeated the immunohistochemical studies using the same antibody used by the Langbein group [ 158 ] and reported staining of multiple unspecific bands in Western blots.…”
Section: Resultsmentioning
confidence: 99%
“…The authors did not provide any specific activities, but complete substrate turnover took as long as 24 hours under conditions, where substrates are completely depleted within a couple of minutes when using authentic human TKT [19]. In further challenge of the postulated role of TKTL1 in tumor cell metabolism, two recent studies could not confirm increased TKTL1 mRNA concentrations in different carcinomas and questioned the validity of the aforementioned immunohistochemical data 16,17. These results match our own observations (Schneider & Tittmann, unpublished) as we could not detect increased TKTL1 transcript levels in cell line HCT116 in contrast to data reported by others [12].…”
Section: Resultsmentioning
confidence: 99%
“…It has been hypothesized that TKTL1 could exhibit enzymatic activity that allows ATP synthesis in hypoxic and cancer cells in a pathway analogous to the phosphoketolase pathway present in some heterofermentative bacteria [12]. However, the presumed key role of TKTL1 in cancer cell metabolism has been put into question in numerous recent studies, where no overexpression of TKTL1 could be detected in several malignant tumor cell lines [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Transketolase-like 1 (TKTL1) has gained increased attention due to several studies showing a TKTL1-positive staining of malignant tumor tissue of different origins [ 15 , 16 , 20 , 22 24 , 35 , 40 , 41 , 43 , 51 ] and its subsequent designation as a “proto-oncogene” [ 9 ]. Furthermore, several cancer cell lines have been reported to be positive for TKTL1 protein upon Western blot analysis [ 7 , 21 , 29 , 52 54 ], cyto-immunohistochemistry [ 50 , 55 ] and RT-qPCR. For example, Sun and coworkers analyzed TKTL1 expression in six HNSCC cell lines via Western blot with the JFC12T10 antibody and found that TKTL1 was relatively overexpressed in two cell lines (FaDU and UM22B) compared with levels in normal mucosal samples [ 29 ].…”
Section: Discussionmentioning
confidence: 99%